On CO2 sequestration in concrete aggregate via carbonation: simulation and experimental verification. Issue 12 (31st August 2022) - Jeong, Jena; Ramézani, Hamidréza; Papadakis, Vagelis G.; Colin, Johan; Izoret, Laurent
Abstract: The paper deals with the assessment of CO2 storage capacity in cement concrete using reactive transport modelling of the accelerated carbonation, i.e. 15 Vol % and experiments. To meet the most realistic geometry of concrete aggregates, the numerical solution is achieved using a homogeneous concrete without aggregates and two-phase concrete including aggregates. We utilise the reactive transport model to estimate molar concentration of cement components and porosity distribution during CO2 carbonation. The model also computes the hydration process before and during carbonation. The numerical solutions are obtained from an extremely nonlinear transient system of Partial Differential Equations (PDEs). The experiments of CO2 carbonation have been carried out using coarse concrete aggregates after 6 months of curing in water. Based on Thermal Gravimetric Analysis (TGA), CO2 uptake during carbonation is determined in weight percent. The numerical simulations fairly agree with the experiments. Highlights: CO2 sequestration calculation via chemical reactions Single-Phase & 2-phase numerical concrete aggregate Accelerated carbonation modelling & experiments. Graphical Abstract: UF0001